Lock your windows: women’s responses to serial rape in a college town - Kendrick, Kristen Ashley (Kansas State University, 2007)
Studies on fear of crime demonstrate that fear of rape controls women’s lives by altering emotions and behavior, though how women construct rape discourse through social networks has not been examined. Further, studies tend to dismiss stranger rape because of its rarity compared to acquaintance rape, but this study argues that research must begin where women are. This study looks to women’s voices to articulate how they talk about fear of rape; specifically, it examines responses to a serial rapist at work in a college town. Framed by feminist methodology, this study establishes the influence of fear on women’s lives and the role of women’s social networks in disseminating information, constructing strategies, and changing behavior as it relates to a local serial rapist. The study utilizes a multi-method approach to quantify levels of fear in the community and to document qualitatively women’s responses to knowledge about the serial rapist. Two surveys, content analysis of local newspapers, and interviews support this research. In particular, group interviews conducted in two environments – campus face-to-face groups and online virtual groups – provide opportunities for young women to voice concerns and report behavioral changes related to the serial rapes. The research demonstrates that women are concerned about insufficient information from formal sources and want more accurate reporting. Women depend heavily on informal networks for information, but it is often incomplete and/or inaccurate and may actually intensify fear. As documented in earlier research, women focus on stranger rape to the neglect of the more common acquaintance rape and tend to strategize in individual terms rather than recognize structural issues. A major finding of this research is that young women actually perceive a change in their own identity as they try to manage fear of rape. However, women’s social networks and, in particular, the increasingly popular online networks, provide a forum from which to try out strategies, build collective discourse, and, in turn, develop greater group consciousness among young women. From the experiences of women in this study, several policy implications are offered for managing fear, including education about the more likely threat of acquaintance rape.
Keywords: Fear of rape; Women's social networks; College culture; Serial rape; Fear of crime; Sociology, Criminology and Penology (0627)